2019
DOI: 10.1002/ente.201900047
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Structured Reactor System for CO2 Methanation under Dynamic Operating Conditions

Abstract: Herein, the use of an additively manufactured rack‐type reactor for CO2 methanation under dynamic operating conditions is proposed. In detail, CO2 methanation using an additively manufactured structured reactor (catalyst: 2.5 wt% Ru/Al2O3/MgO) is reported. The dynamic operation is simulated by changing the reactant flow rates (loads) based on the operation strategy of an electrolyzer connected to a wind farm. Due to the high heat conductivity of the metallic structures, temperature hotspots related to load var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Several experimental studies towards the effect of concentration forcing on the dynamic reactor response for methanation have already been performed at the micro and macro scale (Yadav and Rinker, 1990;Adesina et al, 1995;Klusáček and Stuchlý, 1995;Kreitz et al, 2019a). At the macro scale Stiegler et al (Stiegler et al, 2019) and Theurich et al (Theurich et al, 2020) recently demonstrated experimentally that improved temperature control of an unsteady-state methanation reactor is possible in structured reactors system (Stiegler et al, 2019) or by product recirculation (Theurich et al, 2020). With focus at the micro scale one of the first studies was performed by Van Ho and Harriott (Van Ho, 1980) reporting that the CH 4 response differs for CO 2 and CO methanation.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies towards the effect of concentration forcing on the dynamic reactor response for methanation have already been performed at the micro and macro scale (Yadav and Rinker, 1990;Adesina et al, 1995;Klusáček and Stuchlý, 1995;Kreitz et al, 2019a). At the macro scale Stiegler et al (Stiegler et al, 2019) and Theurich et al (Theurich et al, 2020) recently demonstrated experimentally that improved temperature control of an unsteady-state methanation reactor is possible in structured reactors system (Stiegler et al, 2019) or by product recirculation (Theurich et al, 2020). With focus at the micro scale one of the first studies was performed by Van Ho and Harriott (Van Ho, 1980) reporting that the CH 4 response differs for CO 2 and CO methanation.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to reduce the costs of the hydrogen storage by minimizing upstream storage capacities (up to 8% of the total investment costs can be saved), the unsteady‐state operation of the exothermic methanation reaction is demanded. However, the occurring phenomena and operation strategies under dynamic conditions are not exhaustively addressed in scientific literature thus far, but receive more attention in recent years . One promising approach is adiabatically operated fixed‐bed reactors, which show a good partial and excess load behavior, since the chemical equilibrium is reached within the residence time.…”
Section: Introductionmentioning
confidence: 99%
“…These effects lead individually or together to the loss of active Ru surface area during CO/CO 2 methanation with time on stream. More importantly, it was demonstrated that supported Ru catalysts (Ru/Al 2 O 3 ) are also better catalysts than the corresponding Ni-based catalyst (Ni/Al 2 O 3 ) under dynamic operation conditions involving the variation of reactor load [78,79]. This property is one of the prerequisites for the future decentralized use of CO 2 methanation reactors/stations.…”
Section: Ru-based Catalystsmentioning
confidence: 99%